Phonological Processes in Ekegusii Borrowing: A Constraint-based Approach - Mose, Edinah (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
Phonological processes are at the heart of linguistic borrowing as it has varied phonological systems. It could be seen that the loan words entering the loan language from the source language can hardly be separated from the phonological process because they must be modified to suit the phonology of the loan language. This article analysed the phonological processes realized in Ekegusii borrowing from English using Optimality Theory’s constraint approach. Since this was a phonological study, descriptive linguistic fieldwork was used. The data used in this article was extracted from Mose’s doctoral study, whereby purposive sampling was used to obtain two hundred borrowed segments from the Ekegusii dictionary, then supplemented by introspection. Further, three adult native proficient Ekegusii speakers who were neither too young nor too old and had all their teeth were purposively sampled. The two hundred tokens were then subjected to the sampled speakers through interviews to realize the sound patterns in the Ekegusii borrowing process overtly. The findings revealed that Ekegusii phonological constraints defined the well-formedness of the loanwords by repairing the illicit structures. To fix, various phonological processes were realized. They included: epenthesis, deletion, devoicing/strengthening, voicing/ weakening, re-syllabification, substitution, monophthongization, and lenition. The article concludes that borrowing across languages (related or unrelated) reports similar if not the same phonological processes only that the processes attested in one language are a subset of the universally exhibited phonological processes.